EU accession: A policy window opportunity for nursing?. Issue 3 (March 2017) - De Raeve, Paul; Rafferty, Anne-Marie; Bariball, Louise; Young, Ruth; Boiko, Olga
Highlights: European enlargement has been neglected as a policy issue in nursing. The extent to which nurse leaders used enlargement as a policy window is examined. Case studies of Romania and Croatia were analysed for leadership engagement. Professional leadership need to be aligned to policy goals to optimise impact. Commission mechanisms need to be strengthened to facilitate professional engagement. Abstract: European enlargement has been studied in a wide range of policy areas within and beyond health. Yet the impact of EU enlargement upon one of the largest health professions, nursing, has been largely neglected. This paper aims to explore nurse leadership using a comparative case study method in two former Communist countries, Romania and Croatia. Specifically, it considers the extent to which engagement in the EU accession policy-making process provided a policy window for the leaders to formulate and implement a professional agenda while negotiating EU accession. Findings of qualitative interviews and documentary analysis indicate that the mechanisms used to facilitate the accession process were not successful in achieving compliance with the education standards in the Community Acquis, as highlighted in the criteria on the mutual recognition of professional qualifications set out in Directive 2005/36/EC. EU accession capacity building and accession funds were not deployed efficiently to upgrade Romanian and Croatian nursing education towards meeting EU standards. Conflicting views on accession held by the various nursing stakeholders (nursing regulator, nursing union, governmental chief nurse and the professional association) inhibited the setting of a common policy agenda to achieve compliance with EU standards. The study findings suggest a need to critically review EU accession mechanisms and better align leadership at all governance levels.